Financial Literacy and Knowledge on Intention in Sustainable and Responsible Investment - Nabila Na'ma Aisa; Rintan Nuzul Ainy; Qoryani Syahira (Jurnal Reksa, 2023)
Sustainable and Responsible Investment (SRI) has been growing massively recently. The Indonesia Stock Exchange has launched several indexes regarding companies concerned about Environment, Social, and Governance (ESG). Despite the development of the capital market and business, studies about investors' decisions to invest in SRI products are still limited. The present study aims to investigate the drivers of SRI participation of Indonesian investors. Young people have dominated the number of Indonesian investors. Hence, this study focuses on students as the target population, especially in Yogyakarta. This research is explanatory research, which seeks a causal relationship between the variables. The sampling technique used is convenience sampling. The data was collected through an online questionnaire spread to university students in Yogyakarta. Multiple regression analysis is employed to test the data. Financial literacy and knowledge of SRI positively and significantly impact investment intention in SRI. This research contributes to the literature by adding empirical results on how SRI knowledge and financial literacy affect intention in SRI participation. The result can be used as a reference for financial sector and capital market stakeholders to boost investment in SRI.